Case Report: Identification of a Novel GNAS Mutation and 1p/22q Co-Deletion in a Patient With Multiple Recurrent Meningiomas Sensitive to Sunitinib - Hong, Weiping; Shan, Changguo; Ye, Minting; Yang, Yanying; Wang, Hui; Du, Furong; Zhang, Xing; Song, Chao; Cai, Linbo (Frontiers in Oncology, 2021)
Background Although surgical resection can cure the majority of meningiomas, there are still approximately 20% of patients suffering from an aggressive course with recurrence or progression. In this study, we reported a novel GNAS mutation and 1p/22q co-deletion responding to sunitinib in a patient with multiple recurrent meningiomas. Case Presentation A 53-year-old woman with meningioma was hospitalized due to postoperative tumor progression for 3 weeks. WHO grade I meningioma was pathologically diagnosed after the first three surgeries, but the second recurrence occurred approximately 3 years following the third surgery. Next-generation sequencing was performed on the first two recurrent samples. GNAS mutations and 1p/22q co-deletion were both identified, and amplification at 17q and chromosome 19 was also found in the second recurrent sample, based on which WHO grade II/III meningioma was diagnosed. The lesion in the left cerebellopontine angle area enlarged after use of radiotherapy combined with temozolomide chemotherapy for 2 months. When sunitinib was added, the residual lesions began to lessen and continuously reduced. Conclusion This typical case suggested that timely molecular diagnosis for refractory meningiomas contributed to guiding the molecular classification and clinicians to make more reasonable individualized therapeutic regimens, consequently benefiting the patients. This case report also highlighted the potential role of sunitinib in the treatment of refractory meningiomas.